The National Arabic Language Curriculum Based on Outcome-Based Education at Islamic Religious Higher Education Institutions - Isop Syafei (UIN Sunan Gunung Djati Bandung, 2026)
This study aims to analyze the urgency of implementing Outcome-Based Education (OBE) in the development of the National Arabic Language Curriculum at Islamic Religious Higher Education Institutions, identify relevant learning outcomes for students, design a curriculum model in accordance with higher education standards, and evaluate the challenges and opportunities of its implementation within the scientific and institutional context of PTKI. A descriptive qualitative approach was employed to gain an in-depth understanding of the concept and implementation of the OBE-based National Arabic Language Curriculum in PTKI. Primary data were collected through interviews with lecturers, program managers, and students, while secondary data were obtained from curriculum documents, policies, and academic literature. Data collection techniques included interviews, observations, and document analysis. The data were analyzed interactively through reduction, presentation, and conclusion drawing, which were then linked to OBE theory and the Indonesian National Qualifications Framework (KKNI) standards. The findings indicate that implementing Outcome-Based Education (OBE) in the National Arabic Language Curriculum at PTKI is crucial since the previous curriculum was less application-oriented. OBE requires measurable, contextual learning outcomes aligned with KKNI and SN-Dikti to ensure graduates’ global competitiveness. The curriculum model should cover foundational, scientific, and applicative blocks with performance-based assessment. Despite challenges related to lecturers, facilities, and student heterogeneity, opportunities emerge through policy support, digital technology, and collaboration with national and international Islamic educational institutions.